Early acetaminophen Use and 90-day mortality in ICU patients with ischemic stroke - Piao, Zhi-Sheng; Zhang, Yu-Jia; Li, Gen; Jia, Yi; Cheng, Kun (Frontiers in Pharmacology, 2025)
IntroductionThe impact of acetaminophen on the prognosis of ischemic stroke patients admitted to intensive care units remains unclear. Although acetaminophen is commonly used for fever and pain management, its potential benefits beyond temperature control require further investigation.MethodsUsing the MIMIC-IV database, we retrospectively identified 494 ICU-admitted ischemic stroke patients, of whom 362 (73.28%) received early acetaminophen treatment within 48 h after ICU admission. Patients were stratified based on acetaminophen exposure. Weighted Cox regression was applied after inverse probability of treatment weighting (IPTW) adjustment. Subgroup and sensitivity analyses were performed to assess the consistency of associations.ResultsAfter IPTW adjustment, early acetaminophen use was associated with reduced 30-day mortality (HR 0.54, 95% CI 0.31–0.94, p = 0.030), and reduced 90-day mortality (HR 0.53, 95% CI 0.32–0.87, p = 0.013). There were no significant differences in in-hospital mortality or hospital length of stay. Subgroup analyses revealed no significant interaction effects, suggesting a consistent association across different clinical strata.DiscussionEarly acetaminophen use may be associated with improved survival outcomes in critically ill ischemic stroke patients. These findings highlight the potential therapeutic value of acetaminophen beyond symptomatic treatment, warranting confirmation through prospective, multicenter randomized controlled trials.